Adult weight management across the community: population‐level impact of the LOSE IT to WIN IT challenge. (14th March 2018) - VanWormer, J. J.; Pereira, R. F.; Sillah, A.; Sidebottom, A. C.; Benson, G. A.; Lindberg, R.; Winters, C.; Boucher, J. L.
Summary: Objective: Excess body weight negatively impacts health, but there are few evaluations of low‐intensity weight management challenge programs in defined populations. This study examined weight change in adults who participated in the LOSE IT to WIN IT (LIWI) health challenge in a US community. The community‐level impact on body mass index was also explored. Methods: Body weight was analysed over 1 year in the cohort of LIWI enrolees, stratified by participants who were healthy weight or overweight/obese at baseline. Secondarily, a multiple cross‐sectional analysis compared the 2.5‐year trends in body mass index between community adults who did vs. did not participate in LIWI. Results: LOSE IT to WIN IT participants who were overweight/obese lost a mean (95% confidence interval) 1.6 (1.2, 2.0) kg ( 2%) over 1 year ( p < 0.001), whereas healthy weight participants lost 0.7 (0.3, 1.1) kg. Across the community, LIWI participants and non‐participants both gained 0.4 kg m −2 over the 2.5‐year study period ( p = 0.884). Conclusions: LOSE IT to WIN IT was modestly effective among enrolees, resulting in a small weight loss of 2% over 1 year among those who were overweight/obese. However, LIWI did not impact weight gain in the community. To slow such community‐level weight gain trends, weight management challenges must reach larger fractions of the populations that they target.